2019
DOI: 10.31629/kiprah.v7i1.1344
|View full text |Cite
|
Sign up to set email alerts
|

Profil Pelaksanaan Program Adiwiyata dan Sikap Peduli Lingkungan di SMPN Adiwiyata Tingkat Provinsi di Tanjungpinang Tahun 2018

Abstract: Penelitian ini bertujuan untuk mendeskripsikan pelaksanaan program adiwiyata di SMPN adiwiyata tingkat provinsi yang mencakup 4 komponen program adiwiyata dan mendeskripsikan sikap peduli lingkungan guru dan siswa. Penelitian ini merupakan penelitian kombinasi meliputi penelitian deskriptif kualitatif untuk mendeskripsikan pelaksanaan program adiwiyata menggunakan instrumen rubrik oservasi dan penelitian deskriptif kuantitatif untuk mendeskripsikan sikap peduli lingkungan guru dan siswa menggunakan instrumen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…Creating a healthy ecological system requires long-term efforts. 10 This is in congruence with Rahardjo's 11 study, which showed that learning should focus on promoting students' positive attitude towards the environment. 12 SEA assesses environmental care and measures the environment awareness (EA) of students.…”
Section: Introductionsupporting
confidence: 80%
“…Creating a healthy ecological system requires long-term efforts. 10 This is in congruence with Rahardjo's 11 study, which showed that learning should focus on promoting students' positive attitude towards the environment. 12 SEA assesses environmental care and measures the environment awareness (EA) of students.…”
Section: Introductionsupporting
confidence: 80%
“…The Adiwiyata program is designed to encourage and establish schools so that they can participate in implementing government efforts towards environmental preservation and sustainable development for the benefit of present and future generations, increasing savings in financial resources, and increasing the efficiency of school operational activities. (Afriliani, Muhartati and Hindrasti, 2019;Fitria and Samsia, 2020). SMA Negeri I Limboto is one of the schools in Gorontalo District that has pioneered green schools in academic activities.…”
Section: Resultsmentioning
confidence: 99%
“…Kemudian, mempengaruhi sikap peduli lingkungan siswa terhadap lingkungan sekitar meliputi menjaga kebersihan dan kerapihan tata kelas yang juga menjadi poin penilaian (lihat Gambar 5). Lomba kebersihan kelas merupakan bentuk kegiatan memelihara dan merawat gedung lingkungan sekolah oleh warga sekolah yang menjadi standar dalam kegiatan berbasis partisipatif (Afriliani et al, 2019). Bentuk kegiatan lainnya adalah gotong royong dan piket kebersihan kelas.…”
Section: Pengaruh Duta Asri Terhadap Sikap Peduli Lingkunganunclassified